1995
DOI: 10.1074/jbc.270.15.8474
|View full text |Cite
|
Sign up to set email alerts
|

A Post-translational Modification of the Photosystem II Subunit CP29 Protects Maize from Cold Stress

Abstract: The resistance of maize plants to cold stress has been associated with the appearance of a new chlorophyll a/b binding protein in the thylakoid membrane following chilling treatment in the light. The cold-induced protein has been isolated, characterized by amino acid sequencing, and pulse labeled with radioactive precursors, showing that it is the product of post-translational modification by phosphorylation of the minor chlorophyll a/b protein CP29 rather than the product of a cold-regulated gene or an unproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 46 publications
5
110
0
3
Order By: Relevance
“…IEF allows for detection of small changes in the pI of a protein, which often result from conformational changes, such as ligand binding in both soluble (Ek et al, 1980) and membrane proteins (Ben Or and Chrambach, 1983), or posttranslational modifications, such as phosphorylation in the case of CP29 (Bergantino et al, 1995). The analysis of monomeric LHC proteins in npq2 clearly shows that CP26 migrates at two different pH values, whereas in dark-adapted wild type and npq1 only the more acidic band could be detected ( Figure 5A).…”
Section: What Is the Molecular Basis Of This Quenching Effect?mentioning
confidence: 99%
See 1 more Smart Citation
“…IEF allows for detection of small changes in the pI of a protein, which often result from conformational changes, such as ligand binding in both soluble (Ek et al, 1980) and membrane proteins (Ben Or and Chrambach, 1983), or posttranslational modifications, such as phosphorylation in the case of CP29 (Bergantino et al, 1995). The analysis of monomeric LHC proteins in npq2 clearly shows that CP26 migrates at two different pH values, whereas in dark-adapted wild type and npq1 only the more acidic band could be detected ( Figure 5A).…”
Section: What Is the Molecular Basis Of This Quenching Effect?mentioning
confidence: 99%
“…Changes in the pI of a membrane protein may reveal conformational (Ben Or and Chrambach, 1983) and/or posttranslational modifications, such as phosphorylation (Bergantino et al, 1995), which change the exposed charges of proteins. To verify if zeaxanthin binding was the only cause for the change in pI, recombinant holoproteins were produced by overexpressing At-Lhcb5 cDNA in Escherichia coli and reconstituting in vitro the apoprotein with chlorophyll a and chlorophyll b plus either a mixture of Lute þ Viola þ Neo or Lute þ Zea.…”
Section: Recombinant Cp26 Proteins With Distinct Xanthophyll Compositmentioning
confidence: 99%
“…Because the CP26, CP24, and CP29 complexes bind the majority of the xanthophyll cycle carotenoids, it has been suggested that they constitute the primary site of the NPQ mechanism and, as such, play an important role in regulating energy flow from the bulk LHC IIb to the PS II reaction center. Support for this assignment has emerged from the identification of protonation sites in CP26 and CP29 (27)(28)(29), thought to correspond to the low luminal pH requirement for nonphotochemical quenching, and from the fact that CP29 is reversibly phosphorylated under stress conditions (30), suggesting an involvement in stress resistance.…”
mentioning
confidence: 99%
“…Other protein components that undergo reversible phosphorylation are D1, D2, CP43, and CP29 (Bennett, 1984;Bergantino et al, 1995). The LHCII complex is phosphorylated on the N-terminal Thr by STN7 kinase (Depège et al, 2003), which causes the complex to detach from photosystem II (PSII) in grana regions and its longrange diffusion toward the stroma lamellae.…”
Section: Introductionmentioning
confidence: 99%